The impact of diabetes mellitus on carotid atherosclerosis and arterial stiffness; results from the Corinthia study. (14th October 2021) - Theofilis, P; Oikonomou, E; Lazaros, G; Vogiatzi, G; Goliopoulou, A; Chasikidis, C; Mystakidi, V X; Fountoulakis, P; Christoforatou, E; Tsalamandris, S; Anastasiou, M; Papakonstantinou, M; et al.
Abstract: Background: Evaluation of arterial stiffness and carotid atherosclerotic burden can provide important prognostic information regarding the risk for future cardiovascular events. In that context, we tried to determine those vascular properties of diabetic individuals compared to non-diabetics. Methods: In this analysis of the observational "Corinthia" study, we included 1757 participants with determined diabetic status. Propensity scores were employed to match diabetics to non-diabetics with regards to known cardiovascular risk factors. Carotid ultrasonography was performed to evaluate intima-media thickness (cIMT) across the common carotid arteries and the carotid bulbs as well as carotid plaque burden. Arterial stiffness was estimated via assessment of carotid-to-femoral pulse wave velocity (cfPWV). Results: Diabetic individuals had increased mean cIMT (diabetics: 1.12±0.50mm vs. 0.94±0.38mm, p<0.001) and maximum cIMT (diabetics: 1.50±0.93mm vs. 1.20±0.71mm, p<0.001) when compared to non-diabetics (Figure 1, Panel A and B). Carotid plaque burden was also increased in diabetics (34.4% vs. 19.4% in non-diabetics, p<0.001) while bilateral plaques were observed in 14.2% of diabetics opposed to 8.2% of non-diabetics (p<0.001). Concerning arterial stiffness, individuals with DM had significantly higher values of cfPWV (10.6±3.4m/s vs. 8.8±2.5m/s in non-diabetics, p<0.001) (Figure 1, Panel C). In the propensity-matched cohort, mean cIMT (diabetics: 1.13±0.51mm vs. 0.98±0.38mm, p<0.001) and maximum cIMT (diabetics: 1.53±0.95mm vs. 1.24±0.73mm, p<0.001) were significantly higher in diabetics (Figure 2, Panel A and B), as well as carotid plaque burden (36.6% vs. 21.9% in non-diabetics, p<0.001). Analysis according to territory of cIMT measurement displayed substantial differences in left (diabetics: 1.30±0.76mm vs. non-diabetics: 1.06±0.58mm, p<0.001) and right carotid bulbs (diabetics: 1.30±0.82mm vs. non-diabetics: 1.07±0.57mm, p<0.001) with respect to DM (Figure 2, Panel C) but, unexpectedly, non-significant variations were observed in left (diabetics: 0.97±0.48mm vs. non-diabetics: 0.90±0.42mm, p=0.06) and right common carotid artery (diabetics: 0.95±0.50mm vs. non-diabetics: 0.90±0.40mm, p=0.21) (Figure 2, Panel D). Conclusion: We observed increased carotid artery intima-media thickness and cfPWV in individuals with diabetes mellitus. As opposed to non-diabetics, carotid lesions in diabetics were more pronounced in the carotid bulb and not in the common carotid artery. Our findings may raise awareness regarding the focus of atherosclerotic echocardiographic examination in subjects with diabetes mellitus while the impact of glucose-lowering therapies on these specific vascular lesions merits further assessment. Funding Acknowledgement: Type of funding sources: None.